Feeding behavior of dairy cows in feedlot and fed on crude glycerin levels in the diet - Murilo de Almeida Meneses; Fabiano Ferreira da Silva; Alex Resende Schio; Robério Rodrigues Silva; Dicastro Dias de Souza; Antônio Ferraz Porto Junior (Acta Scientiarum. Animal Sciences, 2014)
Current experiment evaluated the inclusion effect of crude glycerin levels in the diet on the feeding behavior of confined dairy cows. Fifteen crossbred Holsteinx Zebu cows were used, divided into three 5 x 5 Latin squares, with treatments: control (no addition of glycerin) and inclusion of 50, 100, 150 and 200 gcrude glycerin per kg of dry matter (DM) in the diet. The animals were subjected to five visual assessments of feeding behavior for 24 hours in each period. Linear increase on feeding time and rumination and on decrease of idle time with the inclusion of crude glycerin levels (p < 0.05) was reported. There was a linear effect on consumption of dry matter and neutral detergent fiber (NDF) corrected for ash and protein (NDF); a similar effect was registered for intake and ruminating efficiencies of dry matter and NDF with the inclusion of crude glycerin in the diet (p < 0.05). The number of periods and duration of behavioral activities was not affected by the inclusion of crude glycerin (p > 0.05). Crude glycerin did not drastically affect the feeding behavior of dairy cows.